In Silico Study of Green Tea (Camellia sinensis) Compound as Potential Anxiolytic Drug Material Targeting Estrogen Alpha Receptor - Harfiah Nur Aini; Susanti; Richa Mardianingrum (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: The prevalence of anxiety disorders has significantly increased each year but has not been matched by the availability of adequate treatments. Estrogen receptor alpha (ERα) is known to induce anxiety through the activation of a complex system in the body, and drugs that inhibit ERα activity are predicted to have anxiolytic potential. Objective: This study aims to evaluate 50 compounds derived from green tea leaves to discover potential anxiolytic candidates that act by inhibiting ERα. Methods: The research methods used include toxicity screening, pharmacokinetic screening, drug scan, molecular docking, and molecular dynamics. Results: Based on the screening results, quercetin was identified as non-carcinogenic, non-hepatotoxic, easily absorbed, evenly distributed, non-interfering with CYP2D6 enzyme metabolism, and potentially effective as an oral drug. In molecular docking results, quercetin showed a ΔG value of -7.54 kcal/mol and Ki of 2.97 µM, which are better than the reference drug with a ΔG value of -7.20 kcal/mol and Ki of 5.24 µM. Quercetin also shown more stable interactions with the Erα binding site, indicated by amino acids Glu353 and Arg394 in RMSD and RMSF analysis during molecular dynamics simulation. Conclusion: From the study result it can be concluded that quercetin has potential as a good candidate for anxiolytic drug material by inhibiting ERα activity.